2021
DOI: 10.1371/journal.pone.0248995
|View full text |Cite
|
Sign up to set email alerts
|

Non-COVID-19 patients in times of pandemic: Emergency department visits, hospitalizations and cause-specific mortality in Northern Italy

Abstract: The COVID-19 pandemic forced healthcare services organization to adjust to mutating healthcare needs. Not exhaustive data are available on the consequences of this on non-COVID-19 patients. The aim of this study was to assess the impact of the pandemic on non-COVID-19 patients living in a one-million inhabitants’ area in Northern Italy (Bologna Metropolitan Area-BMA), analyzing time trends of Emergency Department (ED) visits, hospitalizations and mortality. We conducted a retrospective observational study usin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
166
4
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(193 citation statements)
references
References 32 publications
20
166
4
3
Order By: Relevance
“…Gender and age were almost equally distributed between the 2 years. ED visits consistently dropped in March (− 52%) and April (− 52%) 2020 during the first pandemic wave as already described in other Italian settings [6][7][8]. During summer, the reduction of SARS-CoV-2 contagion and COVID-19 related-hospitalization rates were associated with a gradual increase in ED presentations.…”
supporting
confidence: 64%
See 1 more Smart Citation
“…Gender and age were almost equally distributed between the 2 years. ED visits consistently dropped in March (− 52%) and April (− 52%) 2020 during the first pandemic wave as already described in other Italian settings [6][7][8]. During summer, the reduction of SARS-CoV-2 contagion and COVID-19 related-hospitalization rates were associated with a gradual increase in ED presentations.…”
supporting
confidence: 64%
“…During the COVID-19 pandemic, a consistent decrease in ED visits has been recorded worldwide. Italy has been the first western country to register a reduction in individuals seeking medical attention in EDs, although studies describing this phenomenon are mostly limited to the first pandemic wave [6][7][8].…”
mentioning
confidence: 99%
“…In a study conducted in TASH before the COVID 19 pandemic, overcrowding was one problem identified hindering the provision of quality care and care within a reasonable time [ 25 ], which might have an implication on implementation of social distancing, which is one of the preventive measures during COVID 19 pandemic [ 20 , 26 ]. Studies conducted during the early stages of COVID in Ethiopia also revealed the problem of inadequate personal protective equipment in major hospitals of Addis Ababa, including TASH [ 38 ]. The overcrowding and the limited availability of personal protective equipment at TASH justifiably increase the fear of acquiring COVID 19 in this setting, which could decline follow-up visits.…”
Section: Discussionmentioning
confidence: 99%
“…Although the admission rate did not significantly decline compared to outpatient follow-up, we will not undermine the decline in a hospital that used to be full with patients waiting to be admitted at any time of the year. In addition, the emergency admission significantly decreased in the study period, which raised the concern of increased morbidity and mortality due to delay or lack of care [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…In countries around the world, SARS CoV-2 dramatically disrupted healthcare systems that often failed to find a balance between maintaining safe routine healthcare for patients with non-COVID-19 disorders and the sudden need for resources to take in the increasing number of patients with COVID-19 [ 4 ]. This competition for resources led to additional COVID-19-related damages, due to complications resulting from uncontrolled disease with increased levels of disability and mortality in non-COVID-19 populations [ 5 ]. Health systems have had little time to prepare and to rapidly reorganize services to meet the acute needs of patients with COVID-19, whilst also maintaining routine and emergency care for people requiring new or ongoing support, and at the same time managing physical distancing and reducing face-to-face appointments and attendance at healthcare establishments.…”
Section: Introductionmentioning
confidence: 99%